Photometric, kinematic, and variability study in the young open cluster NGC 1960. Issue 3 (9th January 2020) - Joshi, Y C; Maurya, J; John, A A; Panchal, A; Joshi, S; Kumar, B
ABSTRACT: We present a comprehensive photometric analysis of a young open cluster NGC 1960 (= M36) along with the long-term variability study of this cluster. Based on the kinematic data of Gaia DR2, the membership probabilities of 3871 stars are ascertained in the cluster field among which 262 stars are found to be cluster members. Considering the kinematic and trigonometric measurements of the cluster members, we estimate a mean cluster parallax of 0.86 ± 0.05 mas and mean proper motions of μRA = −0.143 ± 0.008 mas yr −1 and μDec. = −3.395 ± 0.008 mas yr −1 . We obtain basic parameters of the cluster such as E ( B − V ) = 0.24 ± 0.02 mag, log(Age/yr) = 7.44 ± 0.02, and d = 1.17 ± 0.06 kpc. The mass function slope in the cluster for the stars in the mass range of 0.72–7.32 M⊙ is found to be γ = −1.26 ± 0.19. We find that mass segregation is still taking place in the cluster which is yet to be dynamically relaxed. This work also presents first high-precision variability survey in the central 13 arcmin × 13 arcmin region of the cluster. The V -band photometric data accumulated on 43 nights over a period of more than 3 yr reveals 76 variable stars among which 72 are periodic variables. Among them, 59 are short period ( P < 1 d) and 13 are long period ( P > 1 d). The variable stars have V magnitudes ranging between 9.1 to 19.4 mag and periods between 41 min and 10.74 d. On the basis of their locations in the H–R diagram, periods, and characteristic light curves, 20 periodic variables belong to the cluster are classified as 2 δ-Scuti, 3 γ-Dor, 2 slowly pulsating B stars, 5 rotational variables, 2 non-pulsating B stars, and 6 as miscellaneous variables.